Evaluation of morphometric characteristics of Betwa drainage basin - Kumar, Neetesh; Singh, Jagadish (National Geographical Journal of India, 2021)
The morphometric analysis of any drainage basin is considered useful for water resource studies such as ood assessment, water quality sampling, water use reporting, watershed management etc. Drainage basin is generally dened as the areal extent of land from which the surface runoff ows to a dened drain, channel, stream or river. It is mainly governed by the topography of the terrain. Geographical Information System and Image Processing Techniques can be used for the identication of morphological features and analyzing properties of the basin. The morphometric parameters include linear, areal and relief aspects. 'Watershed Atlas of India' (2014) on 1:50,000 scale is an important digital database for planning and monitoring of development programs on a watershed basis. It serves as a uniform baseline for developing a hydrological unit-based data bank to be used for the management of water resources in the country. Runoff, sedimentation, water balance, evapotranspiration and several other catchment characterization related studies may be taken up on a watershed basis. The present study deals with morphometric parameters such as stream order (Nu), stream length (Lu), bifurcation ratio (Rb), drainage density (D) and stream frequency (Fs) of the Betwa drainage basin. Geographically the basin (77° 30′ to 80° 12′ east longitudes and 23°30′ to 25°55′ north latitudes) is located in two states i.e. Madhya Pradesh and Uttar Pradesh occupying an area of 43780 sq. km. The length of the stream segment is maximum for the rstorder stream and decreases as the stream order increases. This study would help in understanding the hydrological behaviour of the basin. This, in turn, may enable the local people to utilize the resources of the basin for the sustainable development of the area.